Compaction faulting in thick mudstone: a slope stability case study of Prominent Hill open pit mine, South Australia - Fowler, M.J.; Goodchild, D.J. (SSIM 2021: Second International Slope Stability in Mining, 2021)
This case study presents the conditions and performance of a sequence of weak sedimentary rocks at the OZ Minerals Ltd, Prominent Hill open pit mine located in South Australia. The weak rocks form a 100 m thick barren horizontally bedded cover sequence of Permian and Cretaceous age that overlie the ore-bearing Archaean to Mesoproterozoic basement rocks. Mining of the cover sequence rocks occurred in several stages between 2006 and 2012, during which a significant number of large-scale slope instabilities occurred. The failures occurred due to a unique set of geotechnical conditions. All slope instabilities were structurally bound by polygonal faults; a type of compaction discontinuity that occurs in thick, weak, saturated mudstone sequences. We highlight the origin and nature of polygonal faults and implication for slope stability and the engineering geology, geotechnical properties, pore pressure conditions, operational risk management, and design approaches including back and forward analysis. Comprehensive geotechnical monitoring and risk management was successfully employed to maintain safe mining operations. The slope instabilities proved manageable in part due to the long delay between excavation and collapse. A range of operational approaches to managing the instabilities were undertaken including unloading, buttressing, and managed collapse.